A comparison between human-carnivore conflicts and local community attitudes toward carnivores in Westgate Community Conservancy, Samburu, Kenya. Issue 2 (4th March 2019) - Mitchell, Allison M.; Bruyere, Brett L.; Otieno, Tobias O.; Bhalla, Shivani; Teel, Tara L.
ABSTRACT: Human-wildlife conflicts are increasing globally, especially involving livestock depredation by carnivores. To understand the relationship between predation frequency and attitudes toward predators, researchers quantified livestock losses for four carnivore species—African wild dog, spotted hyena, leopard, and lion—as well as attitudes toward these carnivores in Westgate Community Conservancy, Samburu, Kenya. Methods included a three-year data collection period of conflict incidents followed by structured interviews to assess community attitudes. Results demonstrated that livestock depredation mainly involved leopards and spotted hyenas, preying most often on sheep and goats. Attitudes toward lions and hyenas were generally proportionate to their predation involvement. However, the frequency of predation did not always elicit such an expected response, as community members held positive attitudes toward leopards despite their high involvement in conflict, but disliked African wild dogs regardless of their low involvement. The discrepancy in attitudes could be attributed to cultural values, economic losses, and perceived risk.